2011
DOI: 10.1161/hypertensionaha.110.164061
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of Depressive Episodes and Hypertension Over 24 Years

Abstract: Prospective data on depressive symptoms and blood pressure (BP) are scarce, and the impact of age on this association is poorly understood. The present study examines longitudinal trajectories of depressive episodes and the probability of hypertension associated with these trajectories over time. Participants were 6,889 men and 3,413 women London based civil servants, aged 35–55 years at baseline, followed for 24 years between 1985 and 2009. Depressive episode (defined as scoring 4 or more on the General Healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
3
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 84 publications
(61 citation statements)
references
References 38 publications
2
50
3
6
Order By: Relevance
“…Depressive symptoms have been shown to be associated with smoking,28 medication noncompliance,29 and physical inactivity30 as well as diabetes,31 obesity,32 hypertension,33 and inflammation 34. We added to the literature by demonstrating that these factors and others such as antidepressant use35 and corrected QT interval36 do not appear to fully explain the association between depressive symptoms and incident CVD death and stroke in otherwise healthy persons.…”
Section: Discussionmentioning
confidence: 99%
“…Depressive symptoms have been shown to be associated with smoking,28 medication noncompliance,29 and physical inactivity30 as well as diabetes,31 obesity,32 hypertension,33 and inflammation 34. We added to the literature by demonstrating that these factors and others such as antidepressant use35 and corrected QT interval36 do not appear to fully explain the association between depressive symptoms and incident CVD death and stroke in otherwise healthy persons.…”
Section: Discussionmentioning
confidence: 99%
“…‡Estimate not reported as arcsine correction cannot be used, and weighted estimates included CIs with values >1 or <0. of depression between 13% and 17% during patient's lifetime and incidence between 5% and 10%. [17][18][19] It has been reported that medical illness, not only stroke, increases the risk of depression. 20 The World Health…”
Section: Discussionmentioning
confidence: 99%
“…For instance, few studies have included a measure of depression, which is linked to stress but may be associated with a lower BP. 12,13 Another important factor is socioeconomic status (SES), which is negatively associated with hypertension, especially in high-income countries. 14,15 However, studies adjusting for SES do not usually test for a moderation hypothesis (ie, that stress may relate to hypertension to a different extent according to SES).…”
Section: March 2013mentioning
confidence: 99%